Bi-enzyme functionalized electro-chemically reduced transparent graphene oxide platform for triglyceride detection. (30th January 2019) - Bhardwaj, Sheetal K.; Chauhan, Ruchika; Yadav, Premlata; Ghosh, Subhasis; Mahapatro, Ajit K.; Singh, Jay; Basu, Tinku
Abstract : Recently, increased attention has been drawn to application of graphene and its derivatives for construction of biosensors, since they can be used to rapidly detect the presence of bio-analytes. Abstract : Recently, increased attention has been drawn to application of graphene and its derivatives for construction of biosensors, since they can be used to rapidly detect the presence of bio-analytes. Present paper establishes the preparation of a unique transducer which relies on toluidine blue (TB), absorbed by electrochemically reduced graphene oxide (ERGO) transparent thin film onto the surface of the indium tin–oxide (ITO) glass electrode. The proposed TB/ERGO/ITO electrode shows excellent reversible electro-chemical properties. The novel platform has been explored to fabricate a triglyceride (TG) biosensor via co-immobilizing of lipase (LIP) and glycerol dehydrogenase (GDH) onto TB/ERGO/ITO electrode surface. The fabricated bioelectrode (LIP-GDH/TB/ERGO/ITO) directly oxidizes glycerol (produced by catalytic hydrolysis of tributyrin acting as a model TG) in the presence of GDH. The developed bioelectrode replaces unstable biological irreversible redox mediators NAD + /NADH, involved in the triglyceride breakdown reaction. NADH causes fouling on the bioelectrode surface in bi-enzymatic estimation of TG and reduces the shelf-life of biosensor. Electrochemical response studies carried out using cyclic voltammetry reveal that the fabricated electrode can detect tributyrin in the range of 50–400 mg dL −1 with high sensitivity of 29 pA mg −1 dL, low response time of 12 s, long-term stability and a low apparent Michaelis–Menten constant ( K appm) of 0.18 mM, indicating high enzyme affinity of LIP-GDH/TB/ERGO/ITO bioelectrode towards tributyrin. Furthermore, this modified bioelectrode has been explored for estimation of TG with negligible interference in human serum samples. The proposed bi-enzymatic bioelectrode for TG analysis offers an efficient and novel interface for application of graphene and its derivatives in the field of bioelectronic devices.